Studi awal rancangan alat colorimeter menggunakan sensor OPT101 untuk menentukan serapan ekstrak pewarna alami berbasis mikrokontroler arduino (Preliminary study of the colorimeter design using OPT101 sensor to determine the absorption of natural dye extracts based on the Arduino microcontroller) - Puja Kahar; - Yulkifli; - Ramli (Department of Physics – Universitas Negeri Padang UNP, 2019)
Colorimeter is a color measuring instrument used to measure the amount of output voltage produced by each different dye. The dyes used here are red and orange color dyes as the beginning of the experiment. The samples used can be used in hazardous and harmless coloring materials, but in this experiment using non-hazardous artificial materials. The results of the trial output are displayed on the LCD. This tool uses LED as a source of light emitted in samples that are red and orange, then captured by the OPT101 Sensor which converts light into an output voltage. The output voltage is amplified by a voltage amplifier circuit. The results of the output voltage are confirmed on the arduino which is then displayed on the LCD. The program from Arduino is programmed using Arduino software which is then compiled or sent to Arduino which is then displayed on the LCD. The results of the colormetical device were made on a 2.4 volt red sample and an orange sample of 3.13 volts. So that from the measurement results we can distinguish colors from the sample used